PEMBUATAN PUPUK KALIUM-FOSFAT DARI ABU KULIT KAPOK DAN TEPUNG FOSFAT SECARA GRANULASI - Aprilina Purbasari; Faleh Setia Budi (TEKNIK, 2008)
Kapok-husk ash containing + 28% potassium can be used as raw material of potassium-phosphatefertilizer. In this research, kapok-husk ash is mixed with phosphate powder by granulation process toproduce potassium-phosphate fertilizer. Operation variables are granulation time (4, 7, 10 minutes),kapok-husk content (3, 5, 7, 9 %-w/w), and adhesive liquid type (phosphoric acid solution andaquadest). The result shows that the increasing granulation time is proportional to fertilizer yield;the increasing kapok-husk ash content is proportional to potassium content, but inverselyproportional to phosphate content in fertilizer; and phosphoric acid solution is better than aquadestas adhesive liquid referred to fertilizer yield.